Analisis Penerimaan Masyarakat Muslim Boyolali Terhadap Financial Technology Sebagai Alat Transaksi Elektronik - Armi , Pradita Luci; Piliyanti, Indah (Journal of Economics and Business Research (JUEBIR), 2023)
Financial technology (fintech) is a technological development in the financial sector since industrial revolution 4.0 begun. Fintech models is ranging from crowdfunding, peer to peer lending, investment management, payment, market aggregator. The paper argue that finctech is becoming daily lifestyle in urban area. The paper is tested acceptance of fintech as a payment method of 400 rural respondents Boyolali. By united theory of acceptance and use of technology, the study revealed that the variable values of performance expectations, social factors, facilitating conditions show an alpha value of less than 0.05 and the significance value indicates an adequate category, so the results show a relationship with user acceptance, while the effort expectation variable shows an alpha value of more than 0.05 and the significance value is included in the very weak category so that there is no effect on user acceptance. In the test results the moderating variable of experience can strengthen the relationship between social factor variables and conditions that facilitate user acceptance, but the moderating variable cannot strengthen the business expectation variable